Ketamine modulates disrupted in schizophrenia-1/glycogen synthase kinase-3β interaction - Liu, Jia-Ren; Han, Xiao Hui; Yuki, Koichi; Soriano, Sulpicio G. (Frontiers in Molecular Neuroscience, 2024)
Introduction Disrupted in schizophrenia-1 (DISC1) is a scaffolding protein whose mutated form has been linked to schizophrenia, bipolar affective disorders, and recurrent major depression. DISC1 regulates multiple signaling pathways involved in neurite outgrowth and cortical development and binds directly to glycogen synthase kinase-3β (GSK-3β). Since ketamine activates GSK-3β, we examined the impact of ketamine on DISC1 and GSK-3β expression. Methods Postnatal day 7 rat pups were treated with ketamine with and without the non-specific GSK-3β antagonist, lithium. Cleaved-caspase-3, GSK-3β and DISC1 levels were measured by immunoblots and DISC1 co-localization in neurons by immunofluorescence. Binding of DISC1 to GSK-3β was determined by co-immunoprecipitation. Neurite outgrowth was determined by measuring dendrite and axon length in primary neuronal cell cultures treated with ketamine and lithium. Results Ketamine decreased DISC1 in a dose and time-dependent manner. This corresponded to decreases in phosphorylated GSK-3β, which implicates increased GSK-3β activity. Lithium significantly attenuated ketamine-induced decrease in DISC1 levels. Ketamine decreased co-immunoprecipitation of DISC1 with GSK-3β and axonal length. Conclusion These findings confirmed that acute administration of ketamine decreases in DISC1 levels and axonal growth. Lithium reversed this effect. This interaction provides a link between DISC1 and ketamine-induced neurodegeneration.